Heyzine Website-Based E-Comic for Fourth Grade Elementary School Indonesian Language Subjects - Tiara Asti; Sukardi (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
The less-than-optimal use of digital learning media in encouraging students' active participation in learning impacts low student learning outcomes. This research aims to develop e-comic learning media, describe its suitability, and test its effectiveness in supporting student learning outcomes in class IV Indonesian language subjects. The research used is research and development (R&D) using the ADDIE model. The research subjects were 1 material expert and 1 media expert. The test subjects were teachers and fourth-grade elementary school students. The methods used to collect data are observation, interviews, questionnaires, documentation, and tests. The data collection instruments are questionnaires and test questions. The techniques used to analyze data are qualitative and quantitative descriptive analysis. The results of the research are validity tests by material experts with a percentage of 95.3%, media experts with 88.5%, the user (teacher) tests with 94.2%, small-scale trials at 93.3%, and large scale trials with 86.8%, with N-gain score of 61.2%. From these results, it can be concluded that the e-comics developed are feasible, practical, and effective enough to improve student learning outcomes and are used in Indonesian language learning in class IV elementary schools.